Comparison of prolonged rowing on fixed and free-floating ergometers in competitive rowers - Kerhervé, H. A.; Chatel, B.; Reboah, S.; Rossi, J.; Samozino, P.; Messonnier, L. A. (International Journal of Sports Medicine, 2017)
This study aimed to compare the effect of a 40-min submaximal rowing exercise performed on ergometers with fixed and free-floating designs. Heart rate, blood lactate concentration, force and rate of force development (RFD) at the handle, stroke rate, duty factor, movement kinematics of upper and lower limbs, and muscle activity of lumbar spine muscles iliocostalis and erector spinae (IC and ESL) were measured at the beginning and at the end of a 40-min rowing exercise at ~60% of peak power output, in eleven competitive rowers. Force of lumbar extension decreased, and blood lactate increased following submaximal exercise on both ergometers. No changes in RFD, duty factor, and muscle activity of IC occurred in response to submaximal exercise. Rowing on DYN elicited higher heart rate and modified rowing kinematics (stroke rate, acceleration of the lower limbs) without changes in temporal or force application patterns compared to rowing on STAT at the same power output. Rowing on DYN was also associated with increased activity of the lumbar spine muscle ESL, which could originate from a greater range of motion, or from an increased lumbar spine muscle activity, at the same overall power.